Electrical Integration of Human Embryonic Stem Cell-Derived Cardiomyocytes in a Guinea Pig Chronic Infarct Model. (July 2014) - Shiba, Yuji; Filice, Dominic; Fernandes, Sarah; Minami, Elina; Dupras, Sarah K.; Biber, Benjamin Van; Trinh, Peter; Hirota, Yusuke; Gold, Joseph D.; Viswanathan, Mohan; Laflamme, Michael A.
Background: Human embryonic stem cell-derived cardiomyocytes (hESC-CMs) were recently shown to be capable of electromechanical integration following direct injection into intact or recently injured guinea pig hearts, and hESC-CM transplantation in recently injured hearts correlated with improvements in contractile function and a reduction in the incidence of arrhythmias. The present study was aimed at determining the ability of hESC-CMs to integrate and modulate electrical stability following transplantation in a chronic model of cardiac injury. Methods and Results: At 28 days following cardiac cryoinjury, guinea pigs underwent intracardiac injection of hESC-CMs, noncardiac hESC derivatives (non-CMs), or vehicle. Histology confirmed partial remuscularization of the infarct zone in hESC-CM recipients while non-CM recipients showed heterogeneous xenografts. The 3 experimental groups showed no significant difference in the left ventricular dimensions or fractional shortening by echocardiography or in the incidence of spontaneous arrhythmias by telemetric monitoring. Although recipients of hESC-CMs and vehicle showed a similar incidence of arrhythmias induced by programmed electrical stimulation at 4 weeks posttransplantation, non-CM recipients proved to be highly inducible, with a ∼3-fold greater incidence of induced arrhythmias. In parallel studies, we investigated the ability of hESC-CMs to couple with host myocardium in chronically injured hearts by the intravital imaging of hESC-CM grafts that stably expressed a fluorescent reporter of graft activation, the genetically encoded calcium sensor GCaMP3. In this work, we found that only ∼38% (5 of 13) of recipients of GCaMP3+ hESC-CMs showed fluorescent transients that were coupled to the host electrocardiogram. Conclusions: Human embryonic stem cell-derived cardiomyocytes engraft in chronically injured hearts without increasing the incidence of arrhythmias, but their electromechanical integration is more limited than previously reported following their transplantation in a subacute injury model. Moreover, non-CM grafts may promote arrhythmias under certain conditions, a finding that underscores the need for input preparations of high cardiac purity.